IMPLEMENTASI PERATURAN DAERAH NOMOR 8 TAHUN 2023 TENTANG PAJAK DAN RETRIBUSI DAERAH OLEH DINAS PERHUBUNGAN KABUPATEN PANGANDARAN (Studi di Objek Wisata Green Canyon Pangandaran) - Muhammad Fauzi Azhar; Agus Nurulsyam S; Otong Husni Taufiq (JURNAL ILMIAH NUSANTARA, 2025)
This research is motivated by the implementation of Regional Regulation Number 8 of 2023 concerning Regional Taxes and Levies by the Pangandaran Regency Transportation Agency at the Green Canyon Pangandaran Tourist Attraction which has not been optimal. The purpose of this study is to determine the implementation of Regional Regulation Number 8 of 2023 concerning Regional Taxes and Levies by the Pangandaran Regency Transportation Agency at the Green Canyon Pangandaran Tourist Attraction. The method used in this study is descriptive analysis. Informants are 10 people. Data collection techniques are literature studies, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through processing data from interviews and observations to draw conclusions so that they can answer the problems in the research. Based on the research results, it is known that the implementation of Regional Regulation Number 8 of 2023 concerning Regional Taxes and Levies by the Pangandaran Regency Transportation Agency at the Green Canyon Pangandaran tourist attraction has been carried out, although not optimally. This is evidenced by the results of the study, which revealed that of the four dimensions used as measuring instruments in the study, eight indicators have not been optimally implemented due to a lack of clarity regarding the parking levy collection mechanism, resulting in persistent tariff discrepancies in levy collection. This is due to a lack of routine supervision and a lack of adequate budget support to meet the needs of parking attendants.